2021
DOI: 10.1002/mp.15184
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiology of the FLASH effect

Abstract: Radiation exposures at ultra-high dose rates (UHDR) at several orders of magnitude greater than in current clinical radiotherapy have been shown to manifest differential radiobiological responses compared to conventional dose rates (CONV). This has led to studies investigating the application of UHDR for therapeutic advantage (FLASH-RT) which have gained significant interest since the initial discovery in 2014 that demonstrated reduced lung toxicity with equivalent levels of tumour control compared with conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 138 publications
(398 reference statements)
4
104
0
1
Order By: Relevance
“…Under the transient hypoxia hypothesis, this heterogeneity should then introduce a sparing effect also on tumors, which is not supported by the literature [ 9 ]. Second, in vitro studies of normal, non-immortalized cells have shown a sparing effect when irradiated in ambient air conditions (pO2 ≈ 159 mmHg) [ 23 , 24 , 25 , 26 ]. Third, simulation studies and oxygen consumption studies in pure water and cell buffer solutions have also challenged this hypothesis by showing that total oxygen depletion did not occur with the use of FLASH radiation [ 27 , 28 , 29 ].…”
Section: Mechanisms Of the Flash Effectmentioning
confidence: 99%
“…Under the transient hypoxia hypothesis, this heterogeneity should then introduce a sparing effect also on tumors, which is not supported by the literature [ 9 ]. Second, in vitro studies of normal, non-immortalized cells have shown a sparing effect when irradiated in ambient air conditions (pO2 ≈ 159 mmHg) [ 23 , 24 , 25 , 26 ]. Third, simulation studies and oxygen consumption studies in pure water and cell buffer solutions have also challenged this hypothesis by showing that total oxygen depletion did not occur with the use of FLASH radiation [ 27 , 28 , 29 ].…”
Section: Mechanisms Of the Flash Effectmentioning
confidence: 99%
“…Laser-driven proton and heavier ion pulses can deliver several orders of magnitude higher instantaneous dose rates (IDR) than typical conventional (radiofrequency) accelerators, potentially further increasing the differential sparing effect on normal tissue and consequently broadening the therapeutic window for radiotherapy. Access to conventional experimental and medical machines has been rather limited for this type of research [9] while the steady increase in available compact LD particle sources has already started to open up new experimental options for systematic radiobiological studies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high doses of MRT beams are likely to induce high DNA damage-generated 'immunogenic cell death', as has been suggested for FLASH irradiation [36].…”
mentioning
confidence: 95%
“…Similar to the activation of the immune system after heterogenous dose delivery with conventional-source SFRT [37], immune cells in the valleys are spared following MRT and can activate an anti-tumor immune response (manuscript under review). In addition, short-pulse FLASH mode is capable of protecting the majority of local and circulating immune cells [36], thus further contributing to the active recruitment of immune cells to the microbeam paths.…”
mentioning
confidence: 99%
See 1 more Smart Citation